Callorhinus ursinus - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
1. Northern Fur Seal Callorhinus ursinus French: Otarie a fourrure / German: Nordlicher Seebar / Spanish: Lobo marino septentrional Other common names: Alaskan Fur Seal, Pribilof Fur Seal Taxonomy. Phoca ursina Linnaeus, 1758, “Habitat in Camschatcae maritimis inter Asiam & Americam proximam, primario in insula Beringii.” Restricted by O. Thomas in 1911 to “Bering Island.” This species is monotypic. Distribution. N Pacific, including the Bering Sea, Sea of Okhotsk, and Sea of Japan, S to Japan (Honshu), and N Mexico (Baja California). Descriptive notes. Total length up to 210 cm (males) and 150 cm (females); weight 180-270 kg (males) and 40-60 kg (females). Newborns are 60-65 cm and 5.4-6 kg. Dental formula I 3/2, C 1/1, PC 6/5 (x 2) = 36. Northern Fur Seals are extremely sexually dimorphic. Mature males are 30-40% longer and 4-5-5 times heavier than mature females. Flipper characteristics are unique. Top of foreflipper has bare skin, demarcated by sharp line where furstarts on wrist. Hindflippers are relatively longer than on any other otariids’ due to long thin extensions of cartilage on each toe. In both sexes, muzzle is short and curved downward, and nose is small. Ear pinnae are long and prominent and may become bare as an individual reaches an advanced age. Vibrissae are long, often extending past ears. Mature adult Northern Fur Seals have pale vibrissae, subadults have vibrissae that are a mix of pale and black, and young have black vibrissae. Adult males are stocky and have mane of long guard hairs from head to neck, chest, and upper back. Their foreheads appearto rise steeply because crown is enlarged by skull’s sagittal crest. Adult females and subadults are moderately built, and it is hard to determine gender until males reach 4-5 years of age and exceed size of females. Furis very thick, with pale-colored underfur. Males are gray to black, or fur may be dark ruddy brown, and mane may show silvery or blonde tints. Adult females and subadults have more variation in fur color but are often dark gray ...